Integrated Assessment of MIG Welding Parameters on Carbon Steel using RSM Optimisation - Junita, Mohd Said; Faiz, Mohd Turan; Norazlianie, Sazali (Semarak Ilmu Publishing, 2023)
This study explores the effects of parameter optimisation in MIG welding on material properties, weld quality, and bead geometry using an experimental design. The goal is to minimise weld defects and enhance material strength in welded parts. A quadratic second-order regression model predicts optimal process parameters for JIS G3131 hot-rolled carbon steel in MIG buttwelding. Tests include a 3-by-3 orthogonal array for welding current, arc voltage, and welding speed, measuring responses like bead height, bead width, penetration, and flexural strength. NDT X-ray radiography identifies flaws, and durability is assessed through a three-point bending test. The study utilises an experimental design, ANOVA, and regression analysis, predicting flexural strength with a 0.66% error. Additionally, the errors for weld penetration, bead width, and bead height are 1.29%, 2.32%, and 2.45%, respectively. The results highlight improved weld geometry and flexural strength through optimised process parameters, offering valuable insights for metal fabrication.